2022
DOI: 10.1021/acsanm.2c04129
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/BN/Fe/BN Nanocomposites for Highly Efficient Electromagnetic Wave Absorption

Abstract: A rational composition design is important for optimizing impedance matching and enhancing the reflection loss of microwave absorption materials. In this study, a Graphene/BN/Fe/BN nanocomposite was successfully prepared by a facile process, in which the boron nitride (BN) was anchored on the surface of the graphene and iron ball. As a result of the microwave-transparent feature of BN, the impedance matching of the Graphene/BN/Fe/BN nanocomposite was well adjusted by decreasing the dielectric constant and atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Additionally, the remaining three peaks at 286.8, 287.7, and 289.3 eV correspond to the hydroxyl peaks, carbonyl peaks, and carboxyl peaks, respectively, suggesting that residual oxygen-containing functional groups from incomplete pyrolysis of the precursor are present. [36,37] The morphology of Co 3 O 4 nanospheres, Co 3 O 4 nanotubes and their precursors were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) as displayed in Figures S2 and S3 (Supporting Information). As displayed in Figure S2a and b (Supporting Information), the obtained spherical precursor presents dispersed nanospheres with a diameter of ≈600 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the remaining three peaks at 286.8, 287.7, and 289.3 eV correspond to the hydroxyl peaks, carbonyl peaks, and carboxyl peaks, respectively, suggesting that residual oxygen-containing functional groups from incomplete pyrolysis of the precursor are present. [36,37] The morphology of Co 3 O 4 nanospheres, Co 3 O 4 nanotubes and their precursors were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) as displayed in Figures S2 and S3 (Supporting Information). As displayed in Figure S2a and b (Supporting Information), the obtained spherical precursor presents dispersed nanospheres with a diameter of ≈600 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the remaining three peaks at 286.8, 287.7, and 289.3 eV correspond to the hydroxyl peaks, carbonyl peaks, and carboxyl peaks, respectively, suggesting that residual oxygen‐containing functional groups from incomplete pyrolysis of the precursor are present. [ 36,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of hydroxyl groups broadens the peak shape and increases the peak intensity signi cantly, which can be used to judge that the particle size of the crystal becomes smaller. It also can be seen that HLaPc-BNNSs has the peak shape of both h-BN and HLaPc, and the HLaPc-BNNSs hybrid shows a wide (002) peak at 2θ = 27.14 °, and the corresponding layer spacing is 0.2243 nm, which is lower than the diffraction peak of the original BN [25]. It can be explained that the introduction of hyperbranched phthalocyanine reduces the regularity of BN lamellar, increases the layer spacing, decreases the intensity of diffraction peak and widens the peak type.…”
Section: Preparation and Characterization Of Hlapc-bnnssmentioning
confidence: 95%
“…Hexagonal boron nitride ( h -BN) has attracted great attention due to its 2D layered hexagonal honeycomb structure and excellent properties, such as outstanding chemical and thermal stability and mechanical strength, good electric insulation, and ultrahigh thermal conductivity, making it a promising functional filler candidate for polymer-based thermal management materials. Furthermore, some studies have revealed that BN can improve EWA ability to some extent. , On one hand, BN can effectively enhance the impedance matching and improve the EWA performance by adjusting the dielectric properties of materials. On the other hand, as a 2D material, BN in the EWA composites, with an increased number of interface, induces dipole polarization and interface polarization, thereby enhancing EWA performances. Inspired by these insights, a reasonable combination of BN and CNTs may not only improve the EWA ability but also effectively constructs a heat flux pathway, enabling EWA materials to simultaneously have high thermal conductivity . Meanwhile, many reported research studies characterize EWA ability and thermal conductivity properties on different substrates with varying filler loading, which cannot truly reflect the integrated EWA ability and thermal conductivity in one material.…”
Section: Introductionmentioning
confidence: 99%